THE NUTRITIVE VALUES OF PUFA-CONCENTRATE SUPPLEMENTED WITH YEAST AND Curcuma xanthorrhiza Roxb STORED IN SEVERAL WEEKS - Sulistyowati, E.; Sudarman, A.; Wiryawan, K. G.; Toharmat, T. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The PUFA (polyunsaturated fatty acid)-concentrates containing fatty acid sources (roasted corn grain,roasted soy bean meal, and corn oil) was designated as PUFA- concentrate for dairy goat. There werefour PUFA-concentrates, no supplement (PC0), 0.5% or 5 g yeast (PCY), 2% or 20 g curcuma powder(PCC), and 0.5% or 5g yeast with 2% or 20g curcuma powder (PCM). These PUFA-concentrates wereevaluated for nutrients and fatty acid contents during 2, 4, and 6 weeks of storage. The application oftreatments utilized in this research was completely randomized design with repeated measurement andsplit plot statistical analysis. Results showed that the contents of dry matter, organic matter, ether extract,crude protein, N-free extract, gross energy, acid detergent fiber, Ca, P, and Saccharomyces cereviseaewere significantly (P<0.05) remained stable as caused by unchained moisture of PUFA-concentrate withcombined supplements (Y5C20) in the 6 weeks of storage. The total PUFA (P), P/S, monounsaturatedfatty acid (MUFA), and long chained fatty acid contents tended to be high in PUFA-concentrate with 2%or 20 g curcuma powder. Whereas, the PUFA-concentrate with a combination of 0.5% or 5 g yeast and2% or 20 g curcuma powder was higher in unsaturated (U) fat and the ratio of U/S. In conclusion, combining all nutrient performances during the storage of 2 to 6 weeks, the PUFA-concentrate with0.5% or 5 g yeast and 2% or 20 g curcuma powder was considered nutritionally good.